MEMBANGUN BIROKRASI YANG PROFESIONAL - Rosmala Dewi (Universitas Medan Area, 2016)
Since the reform era marked by the end of the New Order, many changes in the system of government of the Republic of Indonesia. During the New Order government system presented in ways that centralized power leads to a powerful president as both head of state and the head of government. Failure of efforts to reorganize the bureaucracy have broad impact on the fate of the people, this is of course an impact on the process of democratization. The fate of the people worse off because of the quality of legal services that are not optimal and non-functioning of legal services will tend to distort the process towards justice and welfare. If want to make improvements and eliminate the bad impression the government, the bureaucracy reform effort is urgent given the vast implications for society. For reform the bureaucracy, such as the need to consider internal measures, align the orientation of the oriented democracy and not on power, bureaucrats determined to strengthen the commitment to change towards the better, to build a new culture because all this bureaucracy has a bad image, rationalization of the bureaucracy towards streamlining efficiency, strengthen the rule of law which is based on a clear and improve the quality of human resources.